风电机组回转支承滚子修形曲线设计方法研究 - 章滔; 阳雪兵; 何录忠; 卜忠颉; 聂威; 李敏 (Jixie qiangdu)
To research the modification of three row cylindrical slew bearing for wind turbine,based on the none-line elastic contact equation,the axial and radial roller-raceway contact models are solved.Analyze the effects of load,tilt Angle and roller modification curve on roller stress distribution and parameter determination with examples,based on the loading characteristics of axial and radial rollers,logarithmic modification and tangent arc modification are proposed respectively,which can support the roller modification of slew bearing for follow wind power design.